Immigration and Oral Health in Older Adults: An Integrative Approach. (July 2021) - Wu, B.; Mao, W.; Qi, X.; Pei, Y.
The aim of this study was to develop an integrative framework on aging, immigration, and oral health. The methodology was a critical review that used immigration as a social determinant framework through which to evaluate its impact on the oral health of older immigrants. We reviewed recent empirical evidence on factors related to oral health in older immigrants. In a systematic search across multiple databases, we identified 12 eligible studies in this review. Among the eligible studies, most were conducted among East Asian immigrants (8 articles), followed by non-Hispanic White/European origin (2 articles), Mexican origins (1 article), and Iran and other Middle East regions (1 article). The research revealed knowledge gaps in the evidence base, including the dynamic relationship between acculturation and oral health, the role of environmental factors on oral health for immigrants, psychosocial stressors and their relationship with oral health, and oral health literacy, norms, and attitude to dental care utilization and oral hygiene practices. The development of the integrative framework suggests the pathways/mechanisms through which immigration exerts influences on oral health in later life. This provides opportunities for researchers, practitioners, and policy makers to gain greater insights into the complex associations between immigration and oral health among older adults.